(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Mitochondrial dynamics are a contraversal issue in hepatocellular carcinoma. The present study tries to illustrate the role of mitochondrial dynamics proteins (mitofusin-2 (Mfn2) and YME1L) in hepatocarcinogenesis. Five groups were used: the control group and three HCC groups (after 8, 16, and 24 weeks from DENA induction). The last group was treated with Sorafenib (SP) (10 mg/kg), via oral gavage for 4 weeks after cancer induction. This study revealed that Mfn-2 was downregulated and YME1l was overexpressed in different HCC groups. This dysregulation of mitochondrial dynamics proteins was associated with high hepatic levels of cyclin D1, MMP-9, and MDA and overexpression of ki67 as well as decreasing the hepatic expression of tissue inhibitor of matrix metalloproteinase-3 (Timp-3) and Bax. To confirm the possible role of Mfn2 and YME1L in HCC, we assessed the effect of sorafenib on these parameters and its related HCC characteristics. Sorafenib corrected the level of Mfn2 and YME1L and decreased tumor cell proliferation as well. We also elucidated that mitochondrial dynamics proteins (Mfn2 and YME1L) could be a good therapeutic target for HCC.